Assessing reinforced pavement performance: Influence of geogrid position, axial stiffness, and applied stress - Tan-Hung Nguyen; Kyra Kamille A. Toledo; Trong Phuoc Huynh (CTU Journal of Innovation and Sustainable Development)
This study examined the performance of pavement, considering geogrid’s position within the pavement layers, geogrid’s axial stiffness, and applied stress through the Plaxis 2D program. Results showed that the position of the geogrid has a significant effect on the pavement performance. Using geogrid at the top of the base layer produced a deformation of 2.357 mm, and one at the top of the subbase had a deformation of 2.433 mm. Thus, the use of geogrid on the top of the base layer could provide the highest effectiveness on the pavement performance. Additionally, the geogrid’s axial stiffness had a slight impact on the performance of reinforced pavement. When the axial stiffness increased 2.5 times, the deformation of the pavement decreased only about 0.061 mm. The response of the stress-strain of the reinforced pavement was found to be nonlinear for the static applied stress and to be linear for the dynamic applied stress. The results obtained in this study were theoretically extracted using finite element analysis and the discussions were based on those. Therefore, further studies for the pavement reinforced with geogrid by experiments in the laboratory and on-site should be carried out to understand the impact of geogrid on pavement performance.